2013
DOI: 10.1016/j.cor.2013.02.013
|View full text |Cite
|
Sign up to set email alerts
|

Improved bounds for large scale capacitated arc routing problem

Abstract: The Capacitated Arc Routing Problem (CARP) stands among the hardest combinatorial problems to solve or to find high quality solutions. This becomes even more true when dealing with large instances. This paper investigates methods to improve on lower and upper bounds of instances on graphs with over two hundred vertices and three hundred edges, dimensions that, today, can be considered of large scale. On the lower bound side, we propose to explore the speed of a dual ascent heuristic to generate capacity cuts. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(36 citation statements)
references
References 29 publications
0
36
0
Order By: Relevance
“…The following DFF have been considered: f The pure CG bound (denoted LB CG ) is determined using an implementation of the method from [23] that optimizes (3.1b). We did not try to generate only elementary routes, we did not apply refined k-cycle reductions or other fancy strengthening methods; one can check that, for F = 0 (pure CARP), our pure CG bound is similar to other pure CG bounds from the literature [16,24].…”
Section: Arc Routing Problems 421 Capacitated Arc-routing With Fixmentioning
confidence: 83%
“…The following DFF have been considered: f The pure CG bound (denoted LB CG ) is determined using an implementation of the method from [23] that optimizes (3.1b). We did not try to generate only elementary routes, we did not apply refined k-cycle reductions or other fancy strengthening methods; one can check that, for F = 0 (pure CARP), our pure CG bound is similar to other pure CG bounds from the literature [16,24].…”
Section: Arc Routing Problems 421 Capacitated Arc-routing With Fixmentioning
confidence: 83%
“…The following row shows the number of comparisons where the algorithm achieves a better average fitness The first column shows the instance name (inst). The second column shows the fitness of the best known (BK) solution for each instance (Martinelli et al 2013). For each version of the algorithm tested the table includes the average fitness of the best solution (avg), the standard deviation (std), the best solution (best) the learning algorithm, without considering the values provided by the FLA techniques.…”
Section: Effectiveness Of the Fla Measuresmentioning
confidence: 99%
“…We consider the results of MAENS* , of MAENS-RDG (Mei et al 2014a) and VND (Mei et al 2014b) and an algorithm combining iterate local search and variable neighbourhood descent (Martinelli et al 2013).…”
Section: Comparison With the State-of-the-artmentioning
confidence: 99%
See 1 more Smart Citation
“…Here, LSCARP is referred to the CARPs with more than 300 edges (i.e., the required edges) to be served. The size of 300 is chosen because previous studies have shown that it is large enough to pose a scalability challenge [11] [12] [13] [14], where the tested algorithms either failed to obtain competitive results [11] [12] [14] or required too much computational time [13].…”
Section: Introductionmentioning
confidence: 99%